PENINGKATAN KOMPETENSI TATA RIAS WISUDA DENGAN KONSEP BARBIE LOOK PADA ANGGOTA PRAMUKA RACANA R.A. KARTINI GUGUS DEPAN 24-414 UNIVERSITAS NEGERI SURABAYA - ayu anggraini; Maspiyah Maspiyah; Biyan Yesi Wilujeng; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2026)
This study was conducted in response to the limited knowledge and practical skills of participants in applying graduation makeup using the Barbie Look concept. The research aimed to describe the implementation of the training, analyze the improvement of participants' competency, and identify participants' responses after the training. A quantitative approach with a quasi-experimental one-group pretest-posttest design was employed. The participants consisted of 30 active female members of Pramuka Racana R.A. Kartini, Universitas Negeri Surabaya. Data were collected through observation, pretest and posttest practical assessments, competency evaluation sheets, and participant response questionnaires. The data were analyzed using descriptive statistics, percentages, N-Gain analysis, and paired-sample t-test. The findings indicated that the training significantly improved participants' competency. The average score increased from 91.50 on the pretest to 100.00 on the posttest, with a high N-Gain value of 1.00 and a significant paired-sample t-test result (p < 0.001). Practical performance reached 91%, while participant responses averaged 95%, indicating a very high level of satisfaction. Therefore, the Barbie Look graduation makeup training effectively improved participants' knowledge, practical skills, and learning outcomes and can serve as an alternative competency development program for university students. Keywords: graduation makeup, Barbie Look, training, competency